Learning Management of Sport and Health Education in the Entire High school in Bima - Shutan Arie Shandi (International Conference on Science, Education, and Technology, 2023)
Bima City, situated in the NTB province, is the location of 15 junior high schools. The objective of this study is to examine how physical education and health teachers handle the learning process in all junior high schools in Bima. The collection of data was accomplished by means of observation, interviews, and documentation, with supervisors, teachers, and students serving as sources of information. The credibility of the data was ensured through triangulation. The analysis encompassed three main stages: data reduction, data presentation, and drawing conclusions. The discoveries demonstrated that the learning management practices of physical education and health teachers in Bima's junior high schools consisted of planning, executing lessons, and evaluating learning outcomes. Although most teachers prepared teaching materials in advance, primarily relying on the subject teacher deliberations for resources, there are still areas that could be enhanced in terms of classroom management, learning resources, and instructional media. The assessment methods employed by teachers in this domain included outcome evaluation and process evaluation.